Effects of Acute Hypoxia on the Determination of Anaerobic Threshold Using the Heart Rate-Work Rate Relationships during Incremental Exercise Tests - Ozcelik, Oguz; Kelestimur, H. (My University, 2004)
Anaerobic threshold which describes the onset of systematic increase in blood lactate concentration is a widely used concept in clinical and sports medicine. A deflection point between heart rate-work rate has been introduced to determine the anaerobic threshold non-invasively. However, some researchers have consistently reported a heart rate deflection at higher work rates, while others have not. The present study was designed to investigate whether the heart rate deflection point accurately predicts the anaerobic threshold under the condition of acute hypoxia. Eight untrained males performed two incremental exercise tests using an electromagnetically braked cycle ergometer: one breathing room air and one breathing 12% O2. The anaerobic threshold was estimated using the V-slope method and determined from the increase in blood lactate and the decrease in standard bicarbonate concentration. This threshold was also estimated by in the heart rate-work rate relationship. Not all subjects exhibited a heart rate deflection. Only two subjects in the control and four subjects in the hypoxia groups showed a heart rate deflection. Additionally, the heart rate deflection point overestimated the anaerobic threshold. In conclusion, the heart rate deflection point was not an accurate predictor of anaerobic threshold and acute hypoxia did not systematically affect the heart rate-work rate relationships.
Keywords: Anaerobic threshold; Exercise test; Heart rate deflection point; Hypoxia